The Influence Of Parents' Socio-Economic Status, Lifestyle, Gender, And Peers On Students' Personal Financial - Ariyanto, Andhika Cahya; Indriasari, Ika; Meiriyanti, Rita (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to determine the influence of parents' socio-economic status, lifestyle, gender, and peers on students' personal financial management. The research employs a quantitative approach using questionnaires as the research instrument. The sample consists of 93 respondents, selected using the probability sampling method since the total population of Management students at PGRI University Semarang from the classes of 2020, 2021, 2022, and 2023 is 1,387. The research data were analyzed using IBM SPSS Statistics 23. This study's data have already passed validity and reliability tests, indicating that the data meet the necessary criteria to proceed to hypothesis testing. The results of this study show that: (1) Parents' socio-economic status affects students' personal financial management, (2) Lifestyle does not affect students' personal financial management, (3) Gender does not affect students' personal financial management, and (4) Peers affect students' personal financial management.